Indigeneity, marginality and the state in Bangladesh homeless at home - Nasir Uddin (Routledge, 2025)
"This book explores the critical linkages between indigeneity, marginality, and the state in Bangladesh. Indigeneity is progressively gaining currency in politics and thereby becoming an active force in the larger context of national activism with transnational patronage and international support. Drawing on comprehensive and solid ethnographic accounts, the book offers a broader understanding of the process of marginalisation and the emergence of new leadership among the Khumi, an indigenous group of Bangladesh. It illuminates how the Khumi have realised their position on the margin of the state within the socioeconomic, political, and ethnic history of the Chittagong Hill Tracts. It also looks at how kin-based social organisations and non-kin-based social relations become bases of power and authority as well as cooperation and reciprocity in Khumi society. Lucid and topical, the book will be of interest to scholars and researchers of indigenous studies, anthropology, social anthropology, sociology, political sciences, international relations, border studies, and South Asian studies, especially those concerned with Bangladesh."
Includes bibliographical references and index
Keywords: Ethnische Beziehungen; Soziale Situation; Nationale Minderheit; Minderheitenpolitik; Chittagong Hill Tracts; Khumi (Southeast Asian people) / Social conditions / Bangladesh; Indigenous peoples / Bangladesh / Social conditions; Bangladesh / Ethnic relations